1999
DOI: 10.1002/(sici)1097-0274(199901)35:1<32::aid-ajim5>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Predictive aspects of the abduction external rotation test among male industrial and office workers

Abstract: Background Nerve compression of the brachial plexus can be provoked by the Abduction External Rotation (AER) test where the arms are held in a “hands‐up” position. Methods The AER test was conducted among 137 male industrial and office workers at baseline and after 5 years follow‐up, together with a medical examination/history and exposure analysis. Nerve conduction measurements in the wrist regions were also made. Results The cumulated incidence of neurological signs during the AER test, was estimated to be 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Clinical examinations are valuable when searching for morbidity contrasts, as they have a higher precision and they usually increase specificity, but on the other hand they decrease sensitivity. Also of note is that specific clinical signs may predict future symptoms, signs and sick leave (Toomingas et al 1999;Viikari-Juntura et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical examinations are valuable when searching for morbidity contrasts, as they have a higher precision and they usually increase specificity, but on the other hand they decrease sensitivity. Also of note is that specific clinical signs may predict future symptoms, signs and sick leave (Toomingas et al 1999;Viikari-Juntura et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Positive responses to the outward abduction test and Roos’ test indicating a brachial plexopathy have been identified in a significant number of symptomatic workers [46,47] with variable prevalence between occupational subgroups. Although these tests should not be considered diagnostic, it has been demonstrated that they can predict future upper limb pain and signs of neuropathy [48]. …”
Section: Discussionmentioning
confidence: 99%